The risk factors of linezolid-induced lactic acidosis: A case report and review. Issue 36 (September 2018) - Mao, Yiyang; Dai, Danping; Jin, Haiying; Wang, Yangyang
Abstract: Background: In recent years, linezolid is increasingly used in multidrug-resistant bacteria therapy. At the same time, linezolid-induced lactic acidosis has been continually reported as a serious side effect. Notably, to our knowledge, there are limited available literatures that evaluate risk factors for linezolid-induced lactic acidosis, and there is no highly reliable study on the relationship between linezolid-induced lactic acidosis and age or gender. However, clinicians need relevant information to advice on the use of linezolid. Therefore, we report on a case of life-threatening lactic acidosis after 3 doses of linezolid exposure and evaluate the risk factors of linezolid-induced lactic acidosis. Methods: Cases of linezolid-induced lactic acidosis reported in PubMed were searched. Several characteristics and data of case numbers and deaths were extracted for analysis. Results: A total of 35 articles including 47 cases were included in this study. Twelve patients (25.5%) died due to linezolid-induced lactic acidosis. At the cut-offs of 7, 14, and 28 days, the mortalities were 27.3%, 20%, and 27.3%. No statistically significant difference was observed according to age and gender. However, the proportion (27.7% and 29.8%) and mortality (30.8% and 35.7%) of male patients were much higher than females in both ≥65 and <65 years old groups (proportion: 15.2% and 23.9%; mortality: 14.3% and 18.2%). Conclusion: The mortality of linezolid-induced lactic acidosis was relatively high. The duration of linezolid use and age might not be risk factors. Gender (specifically, male) might be related to the mortality of linezolid-induced lactic acidosis.